Effects of the Appropriate Addition of Antioxidants from Pinus densiflora and Mentha canadensis Extracts on Methane Emission and Rumen Fermentation - Shin Ja Lee; Ye Jun Lee; Jun Sik Eom; Hyun Sang Kim; You Young Choi; Seong Uk Jo; Suk Nam Kang; Ha Young Park; Do Hyung Kim; Sung Sill Lee (Animals, 2020)
This study aimed to investigate the optimal addition of terpene-based Pinus densiflora and Mentha canadensis extracts, with antioxidant and methane reduction effects, as feed supplements to ruminants. Two cannulated steers (450 ± 30 kg), consuming Timothy Hay and a commercial concentrate (60:40, w/w) twice daily (at 09:00 and 17:30) at 2% of body weight, with free access to water and a mineral block, were used as rumen fluid donors. In vitro fermentation experiments, with Timothy Hay as the substrate, were conducted with P. densiflora and M. canadensis extracts as supplements to achieve concentrations of 30, 50, and 70 mg/L on a Timothy Hay basis. Fibrobacter succinogenes decreased in proportion upon P. densiflora and M. canadensis extract supplementation at 50 mg/L, while the dry matter degradability of the feed was not significantly different (p < 0.05). Methane emission was significantly lower in the 50 and 70 mg/L treatment groups, for both extracts, at 12 h (p < 0.05). Based on methane production and antioxidant activity, our study suggests that 30 mg/L addition is the most appropriate level of supplementation.